Hetaryl-Substituted phosphonium-Iodonium ylides in synthesis of heterocycles - Matveeva, Elena D.; Gleiter, Rolf (The journal of organic chemistry, 2012)
A series of hitherto unknown hetaryl-substituted (in phosphonium part) phosphonium-iodonium ylides were synthesized. The reaction of these mixed phosphonium-iodonium ylides with acetylenes opens a way to new furyl annelated phosphinolines or unusually substituted phosphininofurans.